Impact of Reforms to the Banking Sector: Profitability Perspective (International Journal of Innovative Research in Engineering & Management, 2022)
Any modern economy's lifeline is the  banking industry. It is one of the crucial financial pillars of  the financial system, and its impact on an economy's success  or failure is crucial. A bank is a business that deals in money  and credit and wants to make money. It is a financial  institution that deals in money because it takes deposits from  the public and keeps them safe in its custody. Additionally,  it offers credit. The primary objective of this research is to  determine whether public sector banks, particularly State  Bank of Hyderabad and Andhra Bank, have adhered to the  Narasimham Committee's recommendations and whether  their performance lives up to those expectations.
Keywords: Bank; Commercial Bank; Banking System; Economy; Reforms